PHYLOGENETIC RELATIONSHIPS OF LEPTOBRACHIUM HASSELTII TSCHUDI, 1838 (AMPHIBIA, ANURA, MEGOPHRYIDAE) - DETECTION OF A POSSIBLE CRYPTIC SPECIES - Amir Hamidy; Masafumi Matsui (BRIN Publishing (Penerbit BRIN), 2017)
By examining mitochondrial DNA phylogeny using 2424bp of sequence data 12S rRNA, tRNAval, and 16S rRNA genes, we evaluated the taxonomic relationships among Javan litter frogs Leptobrachium hasseltii from southern Sumatra, Java, and Bali. Leptobrachium hasseltii formed a well-supported monophyletic group, which comprised two major clades. One major clade represented the southern Sumatran and Javan populations and the other consisted of the population from Bali. The Javan and southern Sumatran clade included two subclades: the West Javan-southern Sumatran group and the Central Javan group. The genetic divergence between the two major clades (Bali vs. Java-Sumatra) suggested their separation happen at species level. Further studies using morphological and acoustic data are needed to determine the taxonomic status of Bali population.